THE EFFECTIVENESS OF INQUIRY-BASED LEARNING ON STUDENTS LISTENING COMPREHENSION AT ELEVENTH GRADE OF SMA N 1 JATILAWANG, BANYUMAS - Amalia Nafiaturrahmah; Endang Sartika (Jurnal Citra Pendidikan, 2024)
Listening comprehension is substantial understanding the meaning of English spoken which had various challenges to education. This research aimed to find out the effect of inquiry-based learning on students listening comprehension at eleventh grade of SMA N 1 Jatilawang, Banyumas. The study employed quasi-experimental design. The study's population consists of 395 eleventh-grade students at SMA N 1 Jatilawang. The samples were randomly selected from the population. It was selected as the experimental group of XI A and the control group of XI B. The data of collection used pre-test and post-test. Data analyzed by IBM SPSS Program V.26 for Windows. The independent sample t-test establishes a statistically significant distinction in the average pre-test score between the experimental and control groups, with the experimental class scoring 65.37 and the control class scoring 62.33. The Mann-Whitney U Test showed significant differences in post-test students' listening scores between experimental and control groups, with a sig (2-tailed) value of 0.000, rejecting the hypothesis of no significance (H0) and accepting the hypothesis of significance (Ha). Therefore, the result of this research can be concluded that the effect size increased 57%, suggested there are differences before and after treatment of inquiry-based learning was highly effective for students listening comprehension.